Microscopic Characterization of Fusarium sp. Associated with Yellow Disease of Pepper (Piper nigrum L.) in South Bangka Regency - Lestari, Ayu; Henri, Henri; Sari, Eka; Wahyuni, Tri (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
Pepper production has decreased recently, especially due to yellow diseases of Fusarium sp. Thus, this research aimed to isolate and characterize Fusarium sp. from soil and root of healthy and diseased pepper plants. The sampling technique used was purposive sampling. Soil and root pepper samples were taken from lands in Payung and Ranggung Village, Payung District, South Bangka Regency. There were 3 varieties of pepper plant used, including Petaling 1, Nyelungkup, and Merapin Daun Kecil. The characterization of Fusarium sp. isolate included macroscopic and microscopic observation. Macroscopic observation included colony color, colony base color, and growth rate/colony diameter size (cm), while microscopic observation included hyphae structure, and the shape and size of microconidia, macroconidia, chlamydospore, and conidiophore. The research found 66 isolates of Fusarium genus based on the colony color. Most of the isolates were white or purple and red. Colony color of Fusarium sp. showed white color, which then turned to orange color. All isolates showed septate hyphae. Isolates with macroconidia 3-4 septate and micronidia 0-1 septate showed the character of Fusarium oxysporum, while isolates with macroconidia 3-5 septate and microconidia 0-2 septate showed the character of Fusarium solani.